2016
DOI: 10.1038/ncomms12492
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic torque anomaly in the quantum limit of Weyl semimetals

Abstract: Electrons in materials with linear dispersion behave as massless Weyl- or Dirac-quasiparticles, and continue to intrigue due to their close resemblance to elusive ultra-relativistic particles as well as their potential for future electronics. Yet the experimental signatures of Weyl-fermions are often subtle and indirect, in particular if they coexist with conventional, massive quasiparticles. Here we show a pronounced anomaly in the magnetic torque of the Weyl semimetal NbAs upon entering the quantum limit sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
75
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 29 publications
7
75
2
Order By: Relevance
“…This discovery paves the way for realizing the many predicted exotic topological quantum phenomena of Weyl semimetals in the TaAs class of materials 9,[25][26][27][28][29][30][31][32][33][34] . For any ongoing [35][36][37][42][43][44][45][46][47][48][49][50][51] or future experiments on these materials, systematic knowledge of the band structure and Fermi surface is crucial and fundamental in understanding and interpreting their data and observations. However, surprisingly, a comprehensive study of the band structure details of the TaAs Weyl semimetal family has been lacking.…”
Section: 61mentioning
confidence: 99%
“…This discovery paves the way for realizing the many predicted exotic topological quantum phenomena of Weyl semimetals in the TaAs class of materials 9,[25][26][27][28][29][30][31][32][33][34] . For any ongoing [35][36][37][42][43][44][45][46][47][48][49][50][51] or future experiments on these materials, systematic knowledge of the band structure and Fermi surface is crucial and fundamental in understanding and interpreting their data and observations. However, surprisingly, a comprehensive study of the band structure details of the TaAs Weyl semimetal family has been lacking.…”
Section: 61mentioning
confidence: 99%
“…Trivial metals show an additional Landau diamagnetism arising from the orbital motion of their itinerant electrons. In a previous study of NbAs [18], we showed that topological metals exhibit a low-field paramagnetic response originating from their unique Landau quantization, which for a Dirac fermion in a magnetic field B along z is given bywhere ν is the Landau index, v F the Fermi velocity and γ is the quantum correction term which is 1/2 for trivial metals, but in Dirac systems γ = 0 due to the non-trivial Berry's phase. The Berry's phase associated with this quantization is often used as evidence for the existence of non-trivial topology, which can in principle be extracted from a plot of the Landau indices versus inverse magnetic field [19].…”
mentioning
confidence: 99%
“…As the magnetic field is increased, the growing degeneracy of this Landau level pulls down the total energy of the system, leading to an overall paramagnetic response given by M = −dE/dB. When the quantum limit is exceeded, the chemical potential asymptotically approaches the ν = 0 Landau level and the paramagnetic response diminishes, crossing over to the diamagnetic response expected from fully occupied bands [18]. This shift leads to a kink at the quantum limit which, when combined with the sign change, provides strong evidence for the Dirac nature of the system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The electron pockets with the small extremal cross-sectional areas for H//c in the NbAs-type compounds promise an accessible QL of Weyl semimetals in laboratory-based magnets. Moll et al reported that the magnetic torque of NbAs is negative at low field but positive at high field, with a turn in slope at the QL [75]. The positive torque signal indicates that the system becomes paramagnetic above the QL, in stark contrast to its status as Landau diamagnetic below the QL.…”
Section: Measurements In Extreme Conditionsmentioning
confidence: 99%